Paediatric non-endemic nasopharyngeal carcinoma: our experience at an Indian tertiary teaching hospital - Khushboo Shrivastava; Lucky Sriwastwa; Priyanka Shrivastava; Tirumala Kanakadurga Sripati; Rajiv Kumar Jha (Student's Journal of Health Research Africa, 2023)
Introduction: Nasopharyngeal carcinoma (NPC) is a very uncommon malignant tumour in children under the age of 20. The diagnosis of paediatric NPC is challenging due to its relative rarity. This unusual occurrence is frequently linked to delayed diagnosis, which can result in advanced loco-regional illness. Here, we investigate the clinical manifestations, investigations, and treatment of paediatric nasopharyngeal carcinoma in a nonendemic region.